2019
DOI: 10.1039/c9ra03652k
|View full text |Cite
|
Sign up to set email alerts
|

Subtle structural variation in azine/imine derivatives controls Zn2+sensitivity: ESIPT-CHEF combination for nano-molar detection of Zn2+with DFT support

Abstract: Single crystal X-ray structurally characterised ESIPT-active weakly fluorescent imine and azine derivatives undergo Zn2+ assisted turn ON fluorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…109 PEG segments and DTT units formed stable micelles to help the polymer disseminate in water and preferentially complex with Cu 2+ , making it a fluorescent sensor in aqueous media. Wang et al reported a linear AIE supramolecular polymer (57) from a salicylaldehyde azine-containing pillar [5]arene dimer (55) and an azine-based homoditopic guest (56) and utilized it as a turn-off Cu 2+ sensor [Fig. 14].…”
Section: Azine-polymer Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…109 PEG segments and DTT units formed stable micelles to help the polymer disseminate in water and preferentially complex with Cu 2+ , making it a fluorescent sensor in aqueous media. Wang et al reported a linear AIE supramolecular polymer (57) from a salicylaldehyde azine-containing pillar [5]arene dimer (55) and an azine-based homoditopic guest (56) and utilized it as a turn-off Cu 2+ sensor [Fig. 14].…”
Section: Azine-polymer Sensorsmentioning
confidence: 99%
“…54 Khanra et al further reported a β-naphthol derived azinebased chemosensor (20) for the detection of Zn 2+ ions at the nano-molar level [Table 1, entry 13]. 55 The chelation of Zn 2+ ions with 20 results in chelation-enhanced fluorescence (CHEF) through inhibition of ESIPT and -CNisomerization and an enhanced emission was observed at 495 nm. The probe displayed negligible CHEF in the presence of other metal ions and showed a detection limit as low as 36.16 nM.…”
Section: Metal Ion Sensorsmentioning
confidence: 99%
“…In addition, the role of solvent towards the selectivity and sensitivity of detection is noteworthy [4–5] . The function of a sensor may involve several types of interactions between host and guest like hydrogen bonding, probe‐cation coordination, aggregation, electrostatic interaction, hydrophobic and van der Waal's interactions etc [6–8] . A single probe having significantly different response towards multiple ions is cost effective, time saving and hence, highly desirable for practical application [9–10] .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5] The function of a sensor may involve several types of interactions between host and guest like hydrogen bonding, probe-cation coordination, aggregation, electrostatic interaction, hydrophobic and van der Waal's interactions etc. [6][7][8] A single probe having significantly different response towards multiple ions is cost effective, time saving and hence, highly desirable for practical application. [9][10] As solvent may alter the nature and energy parameters of the receptor, hence can alter the fluorescence response and selectivity, generally termed as solvatochromic effect.…”
Section: Introductionmentioning
confidence: 99%
“…11 On the other hand, abnormal zinc metabolism leads to several health issues, including delayed sexual maturation, prostate cancer, type 2 diabetes mellitus (T2DM), Wilson's disease, amyotrophic lateral sclerosis (ALS), and agerelated macular degeneration (AMD). [12][13][14] It is believed that Zn 2+ homeostasis has some correspondence with the pathology of Alzheimer's disease 15 and other brutal neurological problems, such as cerebral ischemia 4 and epilepsy. 5 Currently, the catalytic activities of metal complexes have acquired signicant attention.…”
Section: Introductionmentioning
confidence: 99%